2020
DOI: 10.5114/aoms.2018.75678
|View full text |Cite
|
Sign up to set email alerts
|

Liver parameters as part of a non-invasive model for prediction of all-cause mortality after myocardial infarction

Abstract: Introduction: Liver parameters are associated with cardiovascular disease risk and severity of stenosis. It is unclear whether liver parameters could predict the long-term outcome of patients after acute myocardial infarction (AMI). We performed an unbiased analysis of the predictive value of serum parameters for long-term prognosis after AMI. Material and methods: In a retrospective, observational, single-center, cohort study, 569 patients after AMI were enrolled and followed up until 6 years for major advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…A few recent studies reported that elevated serum transaminases were independently associated with poor clinical outcomes in patients with AMI. The extent of liver injury, in particular in patients with preexisting metabolic syndrome, may have a direct impact on cardiac outcomes [13]. Hypoxic liver injury (HLI) is commonly diagnosed in the emergency room in patients with STEMI (in 22% of patients), and those patients with HLI have higher mortality rate and higher frequency of major adverse cardiovascular events (MACE) after percutaneous coronary intervention [14].…”
Section: Table 2 Multivariate Analysis Of Variables Associated With Imentioning
confidence: 99%
“…A few recent studies reported that elevated serum transaminases were independently associated with poor clinical outcomes in patients with AMI. The extent of liver injury, in particular in patients with preexisting metabolic syndrome, may have a direct impact on cardiac outcomes [13]. Hypoxic liver injury (HLI) is commonly diagnosed in the emergency room in patients with STEMI (in 22% of patients), and those patients with HLI have higher mortality rate and higher frequency of major adverse cardiovascular events (MACE) after percutaneous coronary intervention [14].…”
Section: Table 2 Multivariate Analysis Of Variables Associated With Imentioning
confidence: 99%
“…Data have shown that cardiovascular diseases are often accompanied by impaired liver function (as a result of reduced arterial perfusion or congestion); hence, this transaminase’s activity as a prognostic factor for morbidity and mortality in cardiovascular patient groups has been the main focus of studies. In a retrospective center study conducted on 569 AMI patients, AST was found to be a predictor factor for cardiac death and MACEs (AMI, unstable angina, TLR or another segment or coronary vessel, stroke and saphenous vein aortocoronary bypass grafting) at 6 years of follow-up, its value being significantly correlated with troponin and myoglobin [ 136 ]. Li et al [ 137 ] reported that, in AMI patients, increased AST was not an independent predictor for in-hospital mortality, in contrast to alanine aminotransferase (ALT), which was found to be a marker of elevated risk of early death, together with older age; increased d-dimers, fibrinogen or fasting plasma glucose; and decreased eGFR.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, ALT reflects the state of organ perfusion and congestion based on cardiac pump function. A clinical trial ( 32 ) involving 105 patients with reduced ejection fraction found that AST/ALT ratio independently predicted the severity of cardiac dysfunction while a large study ( 33 ) also found that elevated ALT not only strongly correlated with MACEs, but also served as an important predictor of long-term mortality in AMI patients. Therefore, the inclusion of ALT as a predictor in the model reflects the organ-organ interactions in STEMI patients with early cardiac decompensation.…”
Section: Discussionmentioning
confidence: 99%